P158 The cost of steroid induced morbidity among severe asthma patients in the UK. (12th November 2015) - Barry, L; Sweeney, J; O'Neill, C; Patterson, C; Price, D; Heaney, L
Abstract : Introduction: Patients with severe asthma are estimated to comprise 5–10% of the total asthma population but contribute disproportionately to the overall burden of disease. A growing body of evidence exists that implicates steroid exposure in morbidity and healthcare costs among this group. Aim: This study sought to quantify the additional healthcare costs associated with steroid exposure among patients with severe asthma. Methods: Data on patients severe asthma (GINA treatment step 5 with ≥4 prescriptions/year oral corticosteroids, n = 808), was obtained from the Optimum Patient Care Research Database (OPCRD) database along with age and gender matched mild/moderate asthma patients (GINA treatment step 2/3, n = 3975) and non-asthmatic controls (rhinitis only, n = 1865) Data included details of all scheduled and unscheduled healthcare consultations and details of prescribed medicines. Data on service use were extracted for the two most recent years for which observations were available. Healthcare contacts were monetised using unit costs extracted from the Personal Social Services Research Unit's reference costs and for drugs using Prescription Cost Analysis data. All costs were expressed in their 2013 equivalents. Sensitivity analyses related to identification of staff providing specific consultations or activity, and high/low estimates based on assumptions used were produced. Mean high/low healthcare costs over two years by group were estimated and compared as were costs estimated separately for healthcare contacts and prescribed medicines. Results: As shown in Table 1 mean per patient drug, healthcare activity and combined drug and activity costs were significantly higher for the severe asthma group relative to the mild/moderate group with asthma and the non-asthma controls in both high and low cost scenarios. The mean difference in combined cost between the severe and non-asthma controls groups was between £5, 031 (low cost) and £5, 545 (high cost) depending on the cost scenario and £4, 098 (low cost) and £4, 510 (high cost) compared to the mild asthma group. Conclusions: Patients with severe asthma matched by age and gender have significantly greater direct healthcare costs compared to patients with mild/moderate asthma and non-asthmatic subjects.